Studding and analyzing wirelessnetworks access points - Al-dhaqm, Arafat (2013)
The purpose of this mini project is to enable the reader to understanding affairs and status of the wireless network in the Perdagangan area (PA) and in the Bangunan Sultan Bazar JB area (BSBJA) in Malaysia. We used wardriving to collect and analyze data to know the encryption technology, authentication scheme, configuration, transmissions speed, network topology and manufacturers which used in these wireless networks. In addition, advantage and disadvantage of the technologies and mechanisms which used to configure the access points of the Wireless.